Physical Activity of Female Students of the University School of Physical Education in Poznan on the Basis of IPAQ — Educational and Social Perspectives (Baltic Journal of Sport and Health Sciences, 2010)
In accordance with WHO’s motto: “my health in my hands”, contemporary approach to health issues concentrates on promoting active lifestyle of an individual. An individual’s lifestyle determines one’s health in 50—60%, (which makes it the most significant factor). Other determinants of an individual’s health – according to Marc Lalonde’s health fieldconcept – are: environment (21%), biomedical (16%), and healthcare services (10%). Physical activity is an essential element of healthy lifestyle. Polish society is characterized by a low level of physical activity. Therefore, it is necessary to take social and educational actions in order to shape attitudes, habits or skills within this range. Currently, particular expectations are directed towards physical education teachers, who are propagating health education in Polish schools. It is essential to instruct teachers, who should not only possess didactic skills, but also (or even primarily) — they should set an example by their own behaviour. Resulting from the above mentioned issue, the aimof this work was to characterize physical activity of female students at the University School of Physical Education in Poznań from the perspective of pro-health influence they might have as future PE teachers. The characteristics ofthe respondents are presented with reference to their place of residence and type of sports discipline they train. The research was based on the International Physical Activity Questionnaire (IPAQ). IPAQ is currently considered to be one of the best questionnaires used to analyse physical activity of people aged 15—69 years. For the analysis presented in this paper the shorter version of the questionnaire was used. It included seven questions concerning all types of physical activity (related to everyday life, work and leisure time). IPAQ is a method which makes use of metabolic equivalent — 1 MET. The research was carried on among female students of the full-time programme, specialization: physical education teacher. The calendar age of the students was 19.8 years. The results based on the analysis revealed that the examined students represented high and sufficient level of physical activity. Students training individual sports, as well as those living in cities with more than 100 000 inhabitants, reached higher values of MET coefficient than other respondentsKeywords: lifestyle, health behaviour, physical activity, IPAQ.